The regulation of investment in utilities : concepts and applications - Alexander, Ian, 1967- (World Bank working paper, 2005)
"This paper reviews the common approaches adopted by regulators to: a) the inclusion and valuation of investment in the regulatory asset base, and b) the allocation of costs of investment between different users as well as between connection and usage charges. The former set of issues are key to the creation of incentives for companies to undertake efficient least-cost investment while the latter address the key concern of how revenues are recovered (and the associated risks for the operator). By understanding these issues and how they relate to the investments that are needed in a sector, regulators have an opportunity to better design regimes able to promote necessary investment."